Intervensi Nyeri Punggung pada Ibu Hamil di Desa Pengelatan - Gozali, Wigutomo; Astini, Nyoman Ayu Dwi; Permadi, M Rizal (International Journal of Natural Science and Engineering, 2020)
The enlargement of the uterus and weight gain in the third trimester of pregnancy then the center of gravity moves forward so that the pregnant woman must adjust her stance. Improper body changes will force additional stretching and fatigue on the body, especially in the back. One of the causes of low back pain is due to hormonal changes that cause changes in the supporting and connecting soft tissues resulting in decreased muscle elasticity and flexibility. The negative impact caused by low back pain is that it can cause a decrease in the quality of life of pregnant women due to disruption of daily physical activities. The research objective was to determine the intensity of pain before and after back pain intervention in two and third trimester pregnant women in Pengelatan Village, Buleleng District, Buleleng Regency. This research is a pre-experimental study with a "One Group Pretest-Postest" design. The sampling method used was total sampling. Data collection by interviews, observation, intervention and pain scale Visual Analog Scale (VAS). Analysis data using the univariate and bevariate analysis using paired t-test. The results of the study were differences in pain intensity before and after respondents in the massage intervention. Pregnant women should routinely do massage therapy to reduce pain.